The Quality and Satisfaction of Police Training in Philippine National Police Regional Training Center 6 - Ledesma, Jasten Aires A.; Tinagan, Romeo R. (Philippine Social Science Journal, 2020)
Police training varies across countries in terms of length, process, and content. Some countries adopt practice-oriented police training while others have theory-oriented police training. Training is necessary, especially in organizations dealing with law enforcement and public safety. It equips the police officers with the necessary skills and knowledge to address the demand for security for modern-day society. Police Training in the Philippines is under the Philippine National Police (PNP) pursuant to R.A. 11279. The Philippine National Police Training Institute (PNPTI) administers the eighteen (18) Regional Training Centers nationwide. In Western Visayas, police training is being carried out by the Regional Training Center (RTC) 6 located in Bacolod City for Police Non-Commissioned Officer (PNCO.) This study intends to assess the level of quality and satisfaction of police training in RTC 6.